Extra Physical Activities Positively Affect Balance in Children Aged 5-11 Years - Elif Nur Surucu; Lina Budrienė (Lithuanian Sports University, 2024)
Background. Extra-physical activities (EPA) are necessary for children because they contribute to the development of motor skills and general development. The aim. To evaluate the effect of EPA on balance, measured with the Bruininks-Oseretsky Test-2 (BOT-2), in children aged 5-11 years old. Methods. This study was designed as a cross-sectional study. Children (n = 68) aged 5-11 years were divided into two groups depending on the activity they participated in. 36 children participated in standard physical education (physical education group, PEG) lessons, and 32 children attended extra-physical activities (EPA). Nine subscales of the BOT-2 balance test were evaluated and compared between balanced PEG and EPA.   Results. An independent sample t-test revealed a significant difference in balance between PEG and EPG (t (66) = -2.2, p = 0.02), with EPG being greater than PEG. A Kruskal-Wallis test revealed no difference in EPA specificity (H = 3.62, df = 6, p = 0.72) or the EPA participation frequency (H (4) = 0.93, p = 0.92). Conclusion. The extra physical activity group performed better in balance than the physical education group. This finding suggests a role for extra physical activity in promoting balance. The frequency and specificity of participation in extra-physical activities did not influence the balance. Keywords: balance, motor skills, motor development, physical activity